Highly Efficient Low‐Frequency Broadband Sound Absorption with a Composite Hybrid Metasurface. Issue 10 (2nd August 2021) - Liang, Qingxuan; Wu, Yutao; Lv, Peiyao; He, Jin; Ma, Fuyin; Chen, Tianning
Abstract : To date, high‐efficiency low‐frequency broadband noise control remains a great challenge in the scientific and engineering community. Herein, a composite acoustic metasurface is proposed that is composed of gradient hybrid unit structure with a perforated panel, coiled‐up cavities, and a separating plate. By controlling the position of the separating plate, a series of broader multistage sound‐absorbing peaks corresponding to different resonant frequencies can be achieved. A highly efficient low‐frequency broadband sound‐absorbing metasurface by combining the multiple unit structures with different absorbing peaks is realized successfully, possessing an average sound absorption coefficient above 0.94 in the range from 470 to 3130 Hz with a subwavelength thickness of only 89.8 mm. Furthermore, the proposed structure maintains a good mechanical performance with the compression elastic modulus of 375.57 MPa due to the designed honeycomb structures. Compared with the traditional sound‐absorbing materials, the composite hybrid honeycomb metasurface can achieve an excellent absorption performance with a simple and stable structure for practical application of low‐frequency noise control. Abstract : A composite hybrid honeycomb metasurface composed of a perforated panel and coiled‐up cavities with separating plates is proposed. The performance of the metasurface is verified by simulation and experiments. The results show that it has advantages in low‐frequency characteristics, working bandwidth, high‐efficiency sound absorption, structural thickness, and mechanical strength, indicating its excellent comprehensive performance.